Rising against Asian hate : one day in March [videorecording (DVD)] - Oh, Sandra, 1971- (PBS, 2022)
Following the aftermath of the March 2021 mass shootings at three spas in Atlanta, this film chronicles how the Asian American community came together to fight back against hate and explores the struggles and triumphs of AAPI communities.